Product-access challenges to menstrual health throughout the COVID-19 pandemic among a cohort of adolescent girls and young women in Nairobi, Kenya - Shannon N. Wood; Rachel Milkovich; Mary Thiongo; Meagan E. Byrne; Bianca Devoto; Grace Wamue-Ngare; Michele R. Decker; Peter Gichangi (EClinicalMedicine, 2022)
Summary: Background: Access to menstrual hygiene products enables positive health for adolescent girls and young women (AGYW). Among AGYW in Nairobi, Kenya, this prospective mixed-methods study characterised menstrual health product-access challenges at two time points during the COVID-19 pandemic; assessed trajectories over the pandemic; and examined factors associated with product-access trajectories. Methods: Data were collected from an AGYW cohort in August–October 2020 and March–June 2021 (n=591). The prevalence of menstrual health product-access challenges was calculated per timepoint, with trajectories characterizing product-access challenges over time. Logistic regression models examined associations with any product-access challenge throughout the pandemic; multinomial and logistic regressions further assessed factors associated with trajectories. Qualitative data contextualize results. Findings: In 2020, 52·0% of AGYW experienced a menstrual health product-access challenge; approximately six months later, this proportion dropped to 30·3%. Product-access challenges during the pandemic were heightened for AGYW with secondary or lower education (aOR=2·40; p<0·001), living with parents (aOR=1·86; p=0·05), not the prime earner (aOR=2·27; p=0·05); and unable to meet their basic needs (aOR=2·25; p<0·001). Between timepoints, 38·0% experienced no product-access challenge and 31·7% resolved, however, 10·2% acquired a challenge and 20·1% experienced sustained challenges. Acquired product-access challenges, compared to no challenges, were concentrated among those living with parents (aOR=3·21; p=0·05); multinomial models further elucidated nuances. Qualitative data indicate deprioritization of menstrual health within household budgets as a contributor. Interpretation: Menstrual health product-access challenges are prevalent among AGYW during the pandemic; barriers were primarily financial. Results may reflect endemic product-access gaps amplified by COVID-specific constraints. Ensuring access to menstrual products is essential to ensure AGYW's health needs. Funding: This work was supported, in whole, by the Bill & Melinda Gates Foundation [010481].